Health effect of public sports services and public health services: empirical evidence from China - Cao, Lin; Cai, Jianguang; Gong, Yanping; Bao, Qingqing; Hu, Junrong; Tang, Ningxiao (Frontiers in Public Health, 2024)
There is no clear explanation for the extraordinary rebound in China’s population mortality over the past decade. This paper utilizes panel data from 31 Chinese provinces from 2010 to 2020 to determine the distinct impacts of public sports services (PSS), public health services (PMS), and their interaction on population mortality. Empirical results show that public sports services significantly reduce mortality. Every unit increase in public sports services reduces mortality by about 2.3%. It is characterized by delayed realization. Public health services were surprisingly associated with a rebound in mortality. Further studies found strong health effect from interaction of public sports and health services. The effect was significantly strengthened in areas with fewer extreme temperatures or developed economy. The findings have important policy implications for the high-quality development of public sports and health services. It also emphasizes integration of sports and medicine and mitigates health risks associated with extreme temperatures.